P2-S1.10 Identifying key elements describing sexual behaviour in the Danish Population: a Qualitative Study. (10th July 2011) - Jørgensen, M J; Maindal, H T; Olesen, F; Andersen, B
Abstract : Background: Surveying the sexual behaviour of the general population serves to identify key points of intervention, monitor the effect of such an intervention and interpret changes in the spread of sexually transmitted infections over time. Validated questionnaires describing sexual behaviour could be adapted from other countries, but due to cultural differences this could result in the need to add additional or other questions in order to describe the important Danish issues sufficiently. With a view to designing and initiating a sexual behaviour surveillance program in Denmark, the aim of this qualitative study was to identify points of particular importance to adolescents' sexual behaviour. Method: We conducted four semi-structured focus group interviews with a total of 19 sexually experienced adolescents aged 18 to 23. Boys and girls were interviewed separately. Each group contained pupils from the same Danish Folk High School, but with different social and educational backgrounds. The interview guide was developed on the basis of literature reviews and hypotheses based on many years of experience with sexually transmitted infections from an epidemiological perspective as well as treatment of patients with sexually transmitted infections. Data were transcribed verbatim and analysed using qualitative description. Results: We identified four major categories of risk behaviour: 1) Alcohol consumption is associated with "no condom use". 2) Nights on the town and meetings in foreign counties or at festivals are associated with one night stands and often lead to unsafe sex. 3) Low self-esteem increases the risk of pushing one's personal boundaries, thus resulting in promiscuous sexual behaviour. 4) Increased sexual experience is associated with lack of condom use. Surprisingly, the informants did not consider drug abuse and internet dating to be triggers of unsafe sex see Abstract P2-S1.10 Figure 1 . Conclusion: Danish adolescents identified four key elements that could lead to unsafe sex. These results differed slightly from our expectations and will be included in a sexual behaviour questionnaire to describe important elements influencing the sexual behaviour of Adolescents.